De Moivre Law Application for the Construction of Mortality Tables Based on Indonesian Mortality Tables 2019 - Elsa Anna Pratiwi; Fitri Indah Ningtyas; Ratna Nur Aini Kamilia; Zahwa Aqila Nabilia Aqila Nabilia; Agung Prabowo (International Journal of Quantitative Research and Modeling, 2022)
The mortality table or often referred to as the life table is the main instrument used by actuaries in building premium and reserve structures for life insurance products, annuities, and pension programs. The mortality table provides a complete description of the mortality rate and life expectancy and shows the pattern of death of a group of people born at the same time based on the age they have reached and plays an important role as a basis for calculating the level of life expectancy in the future. This article aims to find out how to construct a mortality table with reference to the 2019 TMI for men with de Moivre's Law. In the results of the construction with de Moivre's law, the lowest  value occurred at the age of 0 years, namely = 0.00900901, while the highest  value occurred at the age of 110 years, namely  = 1. Based on the construction of the  value in the 2019 TMI for men using de Moivre's law, which is compared with the  value in the 2019 TMI for men, the results tend to be the same.